The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1103/physreva.89.022330
|View full text |Cite
|
Sign up to set email alerts
|

Quantum signaling in cavity QED

Abstract: We consider quantum signaling between two-level quantum systems in a cavity in the perturbative regime of the earliest possible arrival times of the signal. We present two main results: First, we find that, perhaps surprisingly, the analog of amplitude modulated signaling (Alice using her energy eigenstates |g , |e , as in the Fermi problem) is generally suboptimal for communication, namely, e.g., phase-modulated signaling (Alice using, e.g., {|+ , |− } states) overcomes the quantum noise already at a lower or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 26 publications
(56 reference statements)
3
98
0
Order By: Relevance
“…This detector couples locally to a scalar quantum field according to the Unruh-DeWitt model [26], which succeeds in capturing most of the fundamental features of the light-matter interaction when angular momentum exchange does not play a dominant role in the detector's dynamics [13,27,28]. This simple but powerful detector model has been successfully used to analyze information flows in relativistic settings in previous literature [29][30][31][32][33][34]. The model considers the detector to be a two-level quantum system (i.e.…”
Section: Single Detectormentioning
confidence: 99%
“…This detector couples locally to a scalar quantum field according to the Unruh-DeWitt model [26], which succeeds in capturing most of the fundamental features of the light-matter interaction when angular momentum exchange does not play a dominant role in the detector's dynamics [13,27,28]. This simple but powerful detector model has been successfully used to analyze information flows in relativistic settings in previous literature [29][30][31][32][33][34]. The model considers the detector to be a two-level quantum system (i.e.…”
Section: Single Detectormentioning
confidence: 99%
“…This approximation consists of neglecting the dynamics coming from the coupling of the off-resonant modes with the particle detectors. It is easily seen that the effect of the off-resonant modes in the quantum state of a particle detector at leading order in perturbation theory becomes negligible for times much larger than the light-crossing time of the cavity (see, for instance, [24]). …”
Section: Onset Of the Instabilitymentioning
confidence: 99%
“…Whilst looking at the interaction terms themselves (3), Clerk & Sipe [14] demonstrated that the RWA's nonlocality stems from the RWA interaction Hamiltonian's non-locality, a result that is independent of the field measurment device used. This non-locality can then be quantified by the standard approach in Relativistic Quantum Information where we consider the actual communication between two particle detectors under the Unruh-DeWitt interaction (see, among others, [6,7,[15][16][17][18]).…”
Section: Introductionmentioning
confidence: 99%